Humanistic Activity Design Needs Based on Ki Hajar Dewantara’s Philosophy for Elementary Students’ Critical and Creative Thinking - Kamalia Nur Sufro; Puspita Ari Metalin Ika; Purwoko Budi (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
Critical and creative thinking skills are essential competencies for elementary school students. However, classroom practices remain predominantly teacher-centered, limiting students’ opportunities for exploration and reflection. This study aims to analyze the need for designing humanistic learning activities based on Ki Hajar Dewantara’s philosophy as a foundation for developing learning models that foster higher-order thinking skills. A qualitative descriptive approach was employed, involving fifth-grade students at SD Unggulan Nahdlatul Ulama in Pasuruan City. Data were collected through observations, interviews, and document analysis, and analyzed using the Miles and Huberman interactive model. The findings indicate that students tend to be passive, rarely ask questions, and rely heavily on teacher instructions, resulting in underdeveloped critical and creative thinking skills. Moreover, existing learning activities have not adequately reflected humanistic values or the principles of Ing Ngarso Sung Tulada, Ing Madya Mangun Karsa, and Tut Wuri Handayani. These results highlight the urgent need for learning activity designs that are more dialogical, reflective, and emancipatory. The study concludes that a     4humanistic learning design grounded in Ki Hajar Dewantara’s philosophy is necessary to improve learning quality and serves as a conceptual and empirical basis for further research using a design research approach.